HIDDEN CURRICULUM AND RELIGIOUS-EMPATHIC CHARACTER FORMATION: PREVENTING MICRO-BULLYING IN ISLAMIC ELEMENTARY SCHOOL - Taufikin, Taufikin; Zulfah, Lina Indana (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The normalization of micro-bullying in elementary schools often appears through teasing, joking, and subtle social exclusion. This study investigates how religion-based character education at MI Tarbiyatusy Syubban, Pati, Central Java, operates as a hidden curriculum to foster empathy and prevent bullying. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that verbal and social bullying are frequently perceived as harmless jokes, shaped by low student empathy, inconsistent values between home and school, and limited emotional reflection in character education practices. In response, religious education functions not merely as normative instruction but as an implicit process of empathy internalization through teacher exemplarity, social habituation, and a spiritual school environment. This study introduces the concept of the religious-empathic hidden curriculum, referring to the implicit transmission of spiritual values that shape students’ social behavior and emotional sensitivity. The findings extend the theories of Lickona and Bandura by emphasizing the transcendental dimension of empathy formation in children.